Combining local preferences with multi-criteria decision analysis and linear optimisation to develop feasible energy concepts in small communities - R. McKenna; V. Bertsch; Kai Mainzer; Wolf Fichtner (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2016)
In Germany over 700 energy cooperatives were established since 2006 and about 46% of installed renewable energy can be referred to as community energy. Decentralised community energy resources are often abundant in smaller, more rural communities. But these often lack the resources to develop extensive energy concepts and thus exploit these resources in a consistent way. Energy system analysis (ESA) offers useful insights in this context, but many energy system models focus on techno-economic aspects, without considering social aspects such as individual preferences. Much research in previous years has attempted to link social aspects and ESAs, often by employing a combination of ESA and multi-criteria decisions analysis (MCDA) tools. This paper presents an integrated participatory approach to developing feasible energy scenarios for small communities, with a focus on the transferability of the method and the consideration of uncertainties. For one exemplary municipality in south west Germany, stakeholder workshops are combined with ESA and MCDA. A total of eight alternatives for the 2030 energy system are elaborated, which vary in terms of the optimization objective between total costs, CO2 emissions and net energy imports. The three alternatives optimized with respect to just one criteria can be rejected. Instead the community should focus on the remaining intermediate scenarios, which achieve the highest overall performance scores and are stable to variations in the criteria weights. Similarities between these five alternatives mean that concrete recommendations about building-level measures can be derived, supported by simply tools that are made available to the community.
urn:nbn:de:swb:90-715493
Keywords: 330